Botanikai vizsgálatok természetes és telepített kecskelegelőkben - Stilling, Ferenc; Póti, Péter; Pajor, Ferenc; Hajnáczki, Sándor (Gyepgazdálkodási Közlemények, 2022)
There are new challenges for global agriculture due to the changing circumstances in natural and economical world. Many professionals mentioned that our current agricultural methods not suitable to produce proper amount and quality foods. We have to change from the conventional farming to a sustainable agriculture to reach a well performing global agriculture what consist local viable agro systems. The organic farming as one type of sustainable agriculture, is a developing sector where the market and economical competition is growing. There is an opportunity to produce high quality food without additives in Hungary based on the climate, good quality soil as well traditional plant and animal species. The hungarian government set better balance between animal husbandry and arable farming as target and focusing on family farming and organic farming.